Prevalence and spectrum of PIK3 mutations in breast cancer and their correlation with clinicopathological features: A cross-sectional observational study from South India - HS Darling; Rahul Sud; Deep Kumar Raman (Cancer Research, Statistics, and Treatment)
Background: Breast cancer is the leading cause of cancer-related deaths among women worldwide, with evolving treatment strategies. Most research is based on Western data, while India has a large breast cancer burden. Understanding genotypic and phenotypic differences in Indian patients can help refine therapeutic strategies. Objectives: The primary objective of this study was to determine the prevalence and spectrum of PIK3CA mutations in patients with breast cancer. The secondary objectives included evaluating the correlation of PIK3CA mutations with clinicopathological features such as tumor grade, stage, receptor status, molecular subtype, and metastatic pattern. Materials and Methods: This cross-sectional observational study was conducted from October 2021 to September 2023 at the Department of Medical Oncology, Command Hospital Air Force, Bangalore. We analyzed data from newly diagnosed biopsy-proven patients with epithelial breast cancer. Results: Among 273 patients, PIK3CA mutation analysis data were available for 220 patients, with mutations detected in 90 (40.9%). The prevalence of mutations was higher in patients aged≤50 years. High-grade tumors (54.3%) and N3 nodal disease (63.1%) showed significantly higher mutation rates. Mutations were more common in HER2-positive tumors (51.3%, P, 0.022) but had no association with hormone receptor status, Ki-67, or molecular subtype. Exons 9 and 20 harbored most mutations, with H1047R being the most frequent. Stage IV tumors and extraosseous metastases showed higher mutation rates. Liquid biopsy had 100% concordance with somatic testing. Conclusion: PIK3CA mutations are prevalent in Indian patients with breast cancer, with rates slightly higher than global estimates. High nodal burden and advanced-stage tumors showed greater mutation rates, which may have therapeutic implications.